Microphase segregation and selective chain scission of poly(2‐methyl‐2‐oxazoline)‐block‐polystyrene. Issue 12 (11th May 2019) - Tran, Helen; Bergman, Harrison M.; de la Rosa, Victor R.; Maji, Samarendra; Parenti, Kaia R.; Hoogenboom, Richard; Campos, Luis M.
ABSTRACT: Herein, we report the design and synthesis of a block copolymer (BCP) with a high Flory–Huggins interaction parameter to access 10 nm feature sizes for potential lithographic applications. The investigated BCP is poly[(2‐methyl‐2‐oxazoline)‐ block ‐styrene] (PMeOx‐ b ‐PS), where the PMeOx segment functions as a hydrophilic segment. Two BCPs with different molecular weights were prepared using PMeOx as macroinitiator for copper(0) mediated controlled radical polymerization. The thin film self‐assembly of the obtained PMeOx ‐b‐ PS was performed by solvent annealing and investigated by atomic force microscopy. Both polymers formed PMeOx cylinders in a PS matrix with an average cylinder diameter of 10.5 nm. Additionally, the ability of the PMeOx domains to selectively degrade under ultraviolet irradiation was explored. It was shown that scission of the PMeOx block does occur selectively, and furthermore that the degraded domains can be removed while leaving the PS matrix intact. By combining synthetic accessibility, small feature sizes, and a selectively cleavable domain, this new BCP system holds significant promise as a lithographic mask for patterning surfaces with high precision. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 1349–1357 Abstract : A new poly(2‐methyl‐2‐oxazoline) (PMeOx)‐containing diblock copolymer has been shown to self‐assemble with sub‐20 nm feature sizes. The PMeOx domain can be selectively removed from the thin film while preserving pattern fidelity, producing a nanoporous film of potential interest for lithography.